Fungiculture in Termites Is Associated with a Mycolytic Gut Bacterial Community - Haofu Hu (American Society for Microbiology, 2019)
ABSTRACT Termites forage on a range of substrates, and it has been suggested that diet shapes the composition and function of termite gut bacterial communities. Through comparative analyses of gut metagenomes in nine termite species with distinct diets, we characterize bacterial community compositions and use peptide-based functional annotation method to determine biomass-degrading enzymes and the bacterial taxa that encode them. We find that fungus-growing termite guts have relatively more fungal cell wall-degrading enzyme genes, while wood-feeding termite gut communities have relatively more plant cell wall-degrading enzyme genes. Interestingly, wood-feeding termite gut bacterial genes code for abundant chitinolytic enzymes, suggesting that fungal biomass within the decaying wood likely contributes to gut bacterial or termite host nutrition. Across diets, the dominant biomass-degrading enzymes are predominantly coded for by the most abundant bacterial taxa, suggesting tight links between diet and gut community composition, with the most marked difference being the communities coding for the mycolytic capacity of the fungus-growing termite gut. IMPORTANCE Understanding functional capacities of gut microbiomes is important to improve our understanding of symbiotic associations. Here, we use peptide-based functional annotation to show that the gut microbiomes of fungus-farming termites code for a wealth of enzymes that likely target the fungal diet the termites eat. Comparisons to other termites showed that fungus-growing termite guts have relatively more fungal cell wall-degrading enzyme genes, whereas wood-feeding termite gut communities have relatively more plant cell wall-degrading enzyme genes. Across termites with different diets, the dominant biomass-degrading enzymes are predominantly coded for by the most abundant bacterial taxa, suggesting tight links between diet and gut community compositions.